Kinetic study of Huadian oil shale combustion using a multi-stage parallel reaction model. (15th March 2015) - Sun, Youhong; Bai, Fengtian; Lü, Xiaoshu; Jia, Chunxia; Wang, Qing; Guo, Mingyi; Li, Qiang; Guo, Wei
Abstract: This study aimed to explore the combustion kinetics of organic matter in Huadian oil shale using thermogravimetric analysis. Increases in particle size or heating rate shifted the combustion process to a higher temperature, because of mass transfer resistance and thermal hysteresis. An investigation into activation energy using the Coats and Redfern, Starink, and Flynn–Wall–Ozawa methods indicated that oil shale combustion process is controlled by multiple reaction mechanisms. Therefore, multi-stage parallel reaction model and bi-Gaussian distribution function were introduced into the analysis of this complex combustion process. A four-stage parallel reaction model for bitumen, volatiles in kerogen, macromolecules and non-volatiles in kerogen, and fixed carbon was used to characterize the combustion process of organic matter in oil shale. The activation energies showed an increasing trend for the four sub-stages. The mechanism of each sub-stage established by Málek's method showed that the second and third sub-stages of the kerogen combustion proceeded via chemical reaction mechanisms and the 3D Zhuravlev–Lesokin–Tempelman model regardless of particle size and heating rate. This finding revealed the intrinsic reactivity and thermal stability of kerogen combustion. Highlights: Combustion kinetic behaviors of oil shale were investigated. Multi-stage parallel reaction model was used to explore combustion kinetic. Málek's method was utilized to determine the kinetic model. Result showed the intrinsic property and thermal stability of kerogen combustion.